Sistem Informasi Pengelolaan Obat Dan Alat Kontrasepsi Berbasis Web Pada Dinas Pengendalian Penduduk Dan Keluarga Berencana Kota Jambi - Mukhtar, Mukhtar; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2022)
Family planning services are one of the basic health services, so the Ministry of Health has established family planning as one of the mandatory health programs that must be supported. One of the supporting factors for improving the quality of family planning and reproductive health services is the availability of drugs and contraceptives in the family planning warehouse. For this reason, optimal management of drugs and contraceptives is required. The management system for drugs and contraceptives at the Jambi City Population Control and Family Planning Service is still done manually and using Microsoft Office Excel so that the management and reporting of drugs is still not optimal. This research produces a prototype that can be implemented further so as to produce a web-based drug and contraceptive management information system at the Jambi City Population Control and Family Planning Office.